PRE-SERVICE PRIMARY TEACHERS’ ECOLOGICAL FOOTPRINT AWARENESS: ARE THERE DIFFERENCES BASED ON GENDER, EDUCATIONAL LEVEL OF PARENTS, AND LONGEST LIVED PLACE OF RESIDENCE - Bayraktar, Sule (PUPIL: International Journal of Teaching, Education and Learning, 2019)
The purpose of this research is to determine pre-service primary teachers’ level of ecological footprint awareness. The study also investigated whether there are differences in ecological footprint awareness based on gender, educational level of parents, and longest lived place of residence. “Ecological Footprint Awareness Scale” which was developed by Coşkun & Sarıkaya (2014) was employed to collect the data. The scale is a 5 point Likert type instrument which is composed of five dimensions related to food, transportation and residence, water consumption, energy consumption, and waste management. Seventy four pre-service primary teachers in their third year of study in Faculty of Education at a medium size University located at northeast part of Turkey participated in the study. Analysis of the data was performed by employing t-test and one-way analysis of variance (ANOVA) by utilizing SPSS statistical package. Results of the study revealed that the pre-service teachers’ awareness on ecological footprint is at a medium level; highest levels of awareness found in energy (X= 4,15) and water consumption(X= 3, 75) dimensions. Least level of awareness detected in food dimension(X=3,03) of the scale. Results of the study showed that pre-service teachers’ awareness level did not change based on gender with the exception of energy dimension of the scale (t=2,24, p <0.05) in favor of females. The results also showed that ecological awareness level of the pre-service teachers changed based on parents’ education in energy and food dimensions of the scale and did not change based on the place of residence.